Pengaruh Pendapatan Asli daerah Dan dana Perimbangan Terhadap Kemandirian Keuangan Daerah Pada Kabupaten Karawang Tahun 2008-2022 - Agnia Afifah Adha; Solihin Sidik (Jurnal Mirai Management, 2023)
This study aims to determine the effect of regional original income, and balance funds partially and simultaneously on regional financial independence in Karawang regency. This study uses a quantitative research type using primary data and secondary data obtained from the 2008-2022 Budget Realization Report in Karawang Regency. The sample used in this study was saturated sampling with a total of 15 observational data for three years. The results of the study show that Regional Original Income has a positive and significant effect on regional financial independence in Karawang Regency in 2008-2022. Balancing Funds have a negative and significant effect on regional financial independence in Karawang Regency in 2008-2022. significant for Regional Financial Independence in Karawang Regency in 2008-2022.